Review Of Life Safety Equipment At Kmp. Brr Operates Across The Ulee Lheue Crossing - The Aceh Provincial Bulk As An Effort To Improve The Aspects Of Shipping Safety - Anuar Tuip; Doharman Lumban Tungkup; Muhammad Daffa (IWTJ : International Water Transport Journal, 2021)
Safety is on of the important aspects in ferry transportation. safety is shown not only to service users, but also to the ship's crew. In 1996, to be exact, on January 19 in the waters of Ujung Seukeui, Sabang, the ferry KMP. The octopus drowned, the cause of sinking the KMP. Octopus because the ship which is supposed to carry about 200 passengers, carries nearly more than 400 passengers who are transported on the ship. Then the extreme weather and changing climate from the east caused the ship to roll causing 54 passengers to die, 284 passengers missing and only 40 passengers surviving.